Network engineering fundamentals : a hands on guide to the core principles (O'Reilly Media, 2015)
"In this video, network designer and teacher Bruce Hartpence presents an introduction to networking for those who are just getting started or need a refresher. You'll come away with a broad understanding of how networks operate and what's required to build them, along with some knowledge of how to use specific tools to build various topologies. Bruce introduces network standards and vendors, such as ITU-T, IEEE, IETF, Cisco, Juniper, and Avaya, as well as various network components including the Network Interface Card (NIC), access points, routers and switches."--Resource description page.